RELEVANSI NILAI SUSTAINABILITY REPORTING DENGAN NVIVO MEASUREMENT METHOD: BENCHMARKING PENERAPAN PELAPORAN PERUSAHAAN YANG TERDAFTAR DI JOHANNESBURG STOCK EXCHANGE [VALUE RELEVANCE OF SUSTAINABILITY REPORTING WITH NVIVO MEASUREMENT METHOD: BENCHMARKING OF CORPORATES IMPLEMENTATION LISTED ON JOHANNESBURG STOCK EXCHANGE] - Kenny Fernando; Budi Kurniawan; Refianto - (Universitas Pelita Harapan, 2020)
This study aims to examine the effect of applying the Sustainability Reporting (SR) model and its impact on the value relevance of accounting information. In accordance with the title, this research emphasizes the measurement of information in SR by using NVIVO software that measures the level of Sustainability Reporting (NVIVO Measurement Method). The company's reporting model has set foot on the integrated reporting model (Integrated Reporting). However, to implement integrated reporting the company must have implemented the concept of Sustainability Reporting. Many developed and developing countries have begun to adopt the latest SR reporting model. In Indonesia, there are already many state-owned companies implementing SR and IR, however, no one has yet revealed the benefits of the reporting at a time. This examines the company's previous reporting model, namely Sustainability Reporting to reveal evidence of the Sustainability Reporting model by taking an example from South Africa, which has officially adopted both reporting models on the stock exchanges in the country. This study will look at the relationship with the value relevance of accounting information from 2005 to 2010.Bahasa Indonesia Abstrak: Penelitian ini bertujuan untuk menguji pengaruh penerapan model pelaporan Sustainability Reporting (SR) dan dampaknya terhadap relevansi nilai informasi akuntansi. Sesuai dengan judulnya, penelitian ini menekankan pada pengukuran informasi dalam SR dengan menggunakan perangkat lunak NVIVO yang mengukur tingkat pelaporan Sustainability Reporting (Metode Pengukuran NVIVO). Model pelaporan perusahaan telah menginjakkan kaki pada model pelaporan terintegrasi (Integrated Reporting). Nam`un, untuk menerapkan Integrated Reporting (IR), perusahaan harus menerapkan konsep pelaporan keberlanjutan (SR). Banyak negara maju dan berkembang telah mulai mengadopsi model pelaporan terbaru SR. Di Indonesia sendiri, sudah ada banyak perusahaan milik negara yang menerapkan SR dan IR, namun, belum ada yang mengungkapkan manfaat pelaporan pada saat suatu negara. Penelitian ini menguji model pelaporan perusahaan sebelumnya, yaitu SR untuk mengungkap bukti model pelaporan SR dengan mengambil contoh dari Afrika Selatan yang secara resmi mengadopsi kedua model pelaporan di bursa saham pada negara tersebut. Studi ini akan melihat hubungan dengan relevansi nilai informasi akuntansi dari 2005 hingga 2010.